Analisis Penerapan Nilai-Nilai Pancasila Pada Peserta Didik Kelas IV SD Negeri 272 Maluku Tengah - Kohilay, Suriani; Salamor, Lisye; Ritiauw, Samuel Patra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to determine the implementation of Civics learning material "Relationship between Symbols and Precepts of Pancasila" and to determine the application of Pancasila values in class IV students of SD Negeri 272 Maluku Tengah. This research uses qualitative research. The sources of research data are fourth grade teachers and students. Primary data is the result of observation, interviews and secondary data comes from the results of photo documentation when taking data. The data collection techniques used are observation, and interviews. The data validity test technique used uses data collection techniques and data sources. The data analysis technique uses the Miles and Huberman model. The results showed that Civics learning material on the relationship between symbols and precepts of Pancasila went well and learning took place actively. From the average results 19 students or 80% of students have implemented the value of Pancasila from the first to the fifth precept but there are still some values in its implementation that are not maximized, especially indicators. In the indicator of daring to express opinions in the value of deliberation and representation, it has not been implemented optimally because students are not confident with themselves and are afraid of being wrong if their opinions are not correct.